Virological and serological kinetics of SARS-CoV-2 Delta variant vaccine breakthrough infections: a multicentre cohort study. (April 2022) - Chia, Po Ying; Ong, Sean Wei Xiang; Chiew, Calvin J.; Ang, Li Wei; Chavatte, Jean-Marc; Mak, Tze-Minn; Cui, Lin; Kalimuddin, Shirin; Chia, Wan Ni; Tan, Chee Wah; Chai, Louis Yi Ann; Tan, Seow Yen; et al.
Abstract: Objectives: Highly effective vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been developed but variants of concerns are worrisome, especially B.1.617.2 (Delta) which has rapidly spread across the world. We aim to study if vaccination alters virological and serological kinetics in breakthrough infections. Methods: We conducted a multicentre retrospective cohort study of patients in Singapore who had received a licensed mRNA vaccine and been admitted to hospital with B.1.617.2 SARS-CoV-2 infection. We compared clinical features, virological and serological kinetics (anti-nucleocapsid, anti-spike and surrogate virus neutralization titres) between fully vaccinated and unvaccinated individuals. Results: Out of 218 individuals with B.1.617.2 infection, 84 received an mRNA vaccine of which 71 were fully vaccinated, 130 were unvaccinated and four received a non-mRNA vaccine. Despite significantly older age in the vaccine breakthrough group, only 2.8% (2/71) developed severe COVID-19 requiring oxygen supplementation compared with 53.1% (69/130) in the unvaccinated group (p < 0.001). Odds of severe COVID-19 following vaccination were significantly lower (adjusted odds ratio 0.07 95% CI 0.015–0.335, p 0.001). PCR cycle threshold values were similar between vaccinated and unvaccinated groups at diagnosis, but viral loads decreased faster in vaccinated individuals. Early, robust boosting of anti-spike protein antibodies was observed in vaccinated patients; however, these titres were significantly lower against B.1.617.2 than the wildtype vaccine strain. Discussion: The mRNA vaccines are highly effective at preventing symptomatic and severe COVID-19 associated with B.1.617.2 infection. Vaccination is associated with faster decline in viral RNA load and a robust serological response. Vaccination remains a key strategy for control of the COVID-19 pandemic.